Strategies in Journalistic Branding on Social Media: The Inﬂuence of Public and Business Dimensions According to Future Journalists’ Perceptions - López-Meri, Amparo; Alonso-Muñoz, Laura; Casero-Ripollés, Andreu (Communication Today, 2020)
Social media have enabled journalists to promote their work and interact with audiences without the intermediation of their organisation. Branding on social media has become a new competency that journalists have to address. It is considered an indicator of any journalist’s reputation and also a way to face the difﬁculties encountered in the sector. However, there is no research that speciﬁcally focuses on personal branding in the ﬁeld of journalism education. Drawing on the perceptions of future generations of journalists, this research examines the speciﬁc skills, practices, attitudes and personality traits associated with branding on social media. By a quantitative approach based on surveys (n = 262), it aims to identify the most effective strategies that students of journalism can each adopt in building a personal brand. Findings show that the students consider that branding is what makes journalists unique, and is the way to show the character, skills and abilities that differentiate them from other journalists. Regarding the strategies, results indicate that positioning, interaction and content curation are the most valued. By contrast, neither self-promotion of own content nor humanisation skills are highlighted enough. On the other hand, a strong link has been found between the brand and the inﬂuence in society, as well as between the brand and the reformulation of some classic journalistic values and principles. Moreover, despite branding’s origins in the ﬁeld of marketing, future journalists repurpose the concept and value its implications in both the business and public dimensions of journalism equally.